2017
DOI: 10.1016/j.jaip.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Adverse and Hypersensitivity Reactions to Prescription Nonsteroidal Anti-Inflammatory Agents in a Large Health Care System

Abstract: Background Nonsteroidal anti-inflammatory drugs (NSAIDs) are among the most frequently used medications in the United States. NSAID use can be limited by adverse drug reactions (ADRs), including hypersensitivity reactions (HSRs). Objective We aimed to use electronic health record (EHR) data to determine the incidence and predictors of HSRs to prescription NSAIDs. Methods We performed a retrospective cohort study of all adult outpatients in a large healthcare system prescribed diclofenac, indomethacin, nabu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 55 publications
3
41
0
2
Order By: Relevance
“…Therefore, the real prevalence of these cases is probably higher than the estimations found here. A retrospective study using EHR data in Boston (USA) found that 0.3% of outpatients have hypersensitivity reactions to nonsteroidal anti‐inflammatory drugs (NSAIDs) within 1 year of prescription …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, the real prevalence of these cases is probably higher than the estimations found here. A retrospective study using EHR data in Boston (USA) found that 0.3% of outpatients have hypersensitivity reactions to nonsteroidal anti‐inflammatory drugs (NSAIDs) within 1 year of prescription …”
Section: Discussionsupporting
confidence: 84%
“…A retrospective study using EHR data in Boston (USA) found that 0.3% of outpatients have hypersensitivity reactions to nonsteroidal antiinflammatory drugs (NSAIDs) within 1 year of prescription. 19 Skin and subcutaneous tissue disorders and immune system dis- Antibacterials for systemic use (~53%) and anti-inflammatory/antirheumatic products together with analgesics (~19%) were the most frequently reported suspected drugs in the database. These results are in line with findings from other investigations.…”
Section: The Overall 5-year Prevalence For Patients With Hypersensitimentioning
confidence: 99%
“…Recent data support the inclusion of anaphylaxis within the NIUA clinical entity [33]. In our study, 1 patient who presented with anaphylaxis has reacted to more than 1 NSAID.…”
Section: Discussionsupporting
confidence: 55%
“…NSAID‐induced delayed reactions (SNIDRs) are very rare both in adults and in children (Table ). Mild cutaneous reactions are maculopapular and fixed drug eruptions, and more severe ones are acute generalized exanthematous pustulosis, Stevens‐Johnson syndrome/toxic epidermal necrolysis, and drug reaction with eosinophilia and systemic symptoms (DRESS), which may be even life‐threatening.…”
Section: Epidemiology and Clinical Manifestations In Different Phenotmentioning
confidence: 99%
“…NSAIDs, as with all the other drugs, may be associated with several side effects, including drug hypersensitivity reactions (DHRs). In general, DHRs count for nearly 15% of all adverse reactions to drugs, and appear, after each exposure to the specific molecule . NSAIDs are among the most frequently reported drugs associated with hypersensitivity reactions, both in the adult and in the pediatric population .…”
Section: Introductionmentioning
confidence: 99%